Історичний розвиток концепції «самообмежена хвороба» - Яцик, Єлизавета Олександрівна (Харків : Харківський національний університет імені В. Н. Каразіна, 2020)
В сучасній медицині все більше уваги приділяється вивченню концепції «самообмеженої хвороби» («СХ»), основи якої були закладені ще Гіппократом. В XX ст., з швидким розвитком нових методів боротьби з хворобами, а також в умовах підвищення «швидкості життя», лікарі все більше стали покладатися на швидкодіючі та ефективні ліки (особливо антибіотики), не дозволяючи собі розкоші очікування на самовиліковування організму. Втім, розвиток резистентності бактерій до антибіотиків призвів до того, що у 2016 р. на спеціальній сесії Генеральної асамблеї ООН ця проблема була названа однією з найбільших загроз для здоров'я людства, що підштовхнуло як до пошуку нових методів, так і до звернення уваги на давно забутий гіппократівський підхід. Це зробило питання виникнення та розвитку концепції «СХ» актуальною темою для дослідження. Ставлення лікарів до концепції «СХ» в історії залежало від розвитку медицини: медичні успіхи призводили до її забуття, а кризи, навпаки, відроджували інтерес до неї. Сучасна зацікавленість «СХ» викликана новою терапевтичною кризою – бактеріальною резистентністю. Певні невдачі, пов’язані з неетичними експериментами в минулому, нашкодили вірі лікарів в цей підхід, але наше розуміння концепції Гіппократа значно удосконалилося, що робить цей підхід більш безпечним та перспективним, ніж це було раніше.

In modern medicine, more and more attention is being paid to the study of the concept of "self-limited disease" (SLD), the foundations of which were laid by Hippocrates. In the XX century, with the rapid development of new methods of combating diseases, as well as the increase in the "speed of life," doctors increasingly began to rely on fast-acting and effective drugs (especially antibiotics), not allowing themselves the luxury of waiting for the body to heal itself. However, the development of bacterial resistance to antibiotics led to the fact that in 2016, at a special session of the UN General Assembly, this problem was called one of the greatest threats to human health, which prompted both the search for new methods and attention to the long-forgotten Hippocratic approach. This has made the issue of the emergence and development of the concept of "health care" a relevant topic for research. The attitude of doctors to the concept of "health care" in history depended on the development of medicine: medical successes led to its oblivion, and crises, on the contrary, revived interest in it. Today's interest in the concept of "SW" is caused by a new therapeutic crisis - bacterial resistance. Certain failures related to unethical experiments in the past have damaged physicians' faith in this approach, but our understanding of the Hippocratic concept has improved significantly, making this approach safer and more promising than it was before.
Historical development of the concept of "self-limited desease"
Keywords: MEDICINE; MEDICINE::Microbiology, immunology, infectious diseases; HUMANITIES and RELIGION; HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of medicine; резистентність бактерій до антибіотиків; самовиліковування організму; resistance of bacteria to antibiotics; self-healing of the body